A thermal simulation tool for CubeSats for dynamic in-orbit scenarios, verified with flight data from the nSight-1 mission - Kearney, Mike-Alec (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.